2007
DOI: 10.1038/cr.2007.39
|View full text |Cite
|
Sign up to set email alerts
|

CIPK9: a calcium sensor-interacting protein kinase required for low-potassium tolerance in Arabidopsis

Abstract: Potassium is one of the major macro-nutrients essential for a number of cellular processes in plants. Low potassium level in the soil represents a limiting factor for crop production. Recent studies have identified potassium transporters that are involved in potassium acquisition, and some of them are critical for potassium nutrition under low potassium conditions. However, little is understood on the molecular components involved in low potassium signaling and responses. We report here the identification of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
119
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(123 citation statements)
references
References 52 publications
2
119
0
1
Order By: Relevance
“…In this study, we revealed a novel role of subclass III SnRK2s in plant growth under high external Mg 2+ concentrations. Previous studies on CIPK26/3/9/23 have characterized the diverse and distinct functions of each of these CIPK genes (Kim et al, 2003;Li et al, 2006;Xu et al, 2006;Cheong et al, 2007;Pandey et al, 2007;Drerup et al, 2013;Kimura et al, 2013;Lyzenga et al, 2013). Other than the individual functions of CIPK26, CIPK3, CIPK9, and CIPK23, it seems that these CIPK genes also have some overlapping functions in planta, because CIPK26/3/9/23 formed a monophyletic group in the phylogenetic analysis (Supplemental Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we revealed a novel role of subclass III SnRK2s in plant growth under high external Mg 2+ concentrations. Previous studies on CIPK26/3/9/23 have characterized the diverse and distinct functions of each of these CIPK genes (Kim et al, 2003;Li et al, 2006;Xu et al, 2006;Cheong et al, 2007;Pandey et al, 2007;Drerup et al, 2013;Kimura et al, 2013;Lyzenga et al, 2013). Other than the individual functions of CIPK26, CIPK3, CIPK9, and CIPK23, it seems that these CIPK genes also have some overlapping functions in planta, because CIPK26/3/9/23 formed a monophyletic group in the phylogenetic analysis (Supplemental Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The ectopic expression of CIPK8 exhibits resistance to high glucose concentrations (Gong et al, 2002). CIPK9 and CIPK23 activate K + channels or transporters, and regulate K + uptake under low K + stress (Xu et al, 2006;Pandey et al, 2007;Liu et al, 2013). SOS2/CIPK24 is critical for salt tolerance, maintaining Na + and Ca 2+ homeostasis (Cheng et al, 2004;Qiu et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…[17][18][19] In addition to its co-localization with the plasma membrane tethered AtTLP family protein AtTLP11, 9,16 YFP-NHL6 fusion proteins were also observed in the cytosol and on the membrane of small vacuole or vesicles, when transiently expressed in tobacco leaf epidermal cells (Fig. 1A).…”
mentioning
confidence: 99%